Joint Effects of Carbon Black Exposure and Dietary Antioxidant Vitamin Intake on Small Airway Dysfunction - Wang, Tao; Li, Jianyu; Liang, Yi; Han, Wei; Tang, Jinglong; Cheng, Guo; Zheng, Yuxin (Frontiers in Nutrition, 2021)
Objectives: Small airway dysfunction is considered as a precursor of chronic obstructive pulmonary disease and asthma. Our aim was to explore the joint effects of carbon black (CB) exposure and antioxidant vitamin intake on small airway dysfunction. Methods: A total of 70 CB packers (CBP) and 107 non-CBPs were enrolled from an established cohort of CBP. Carbon content in airway macrophage (CCAM) quantified in induced sputum was used as a bio-effective dosimetry for exposure to CB. Logistic regression models were used to examine the odds ratios (OR) of CB and dietary intake of antioxidant vitamins on small airway dysfunction, as well as the dose-response association. Results: The prevalence of small airway dysfunction was 32.9% (23 of 70) among CBPs, and 19.6% (21 of 107) among non-CBPs. For each 2.72-fold increase in CCAM, the OR of small airway dysfunction was 2.31 (95% CI = 1.20 to 4.44). For every 10 mg·day-1 increase of the vitamin C intake, the risk of small airway dysfunction decreased by 6% (OR = 0.94, 95% CI = 0.88 to 0.99). Compared to non-CB exposure and higher vitamin C intake, CB exposure and lower vitamin C intake (OR = 6.68, 95% CI = 1.66 to 26.92) were associated with an increased risk of small airway dysfunction. Conclusions: Chronic exposure to a high level of CB aerosol increased the risk of small airway dysfunction in CB baggers. Dietary intake of vitamin C might be a modifiable factor for preventing small airway dysfunction.